Development of Resistant Starch-Pectin Microsphere for Improving Oral Colon-specific Drug Delivery of 5-Fluorouracil (Bangladesh Pharmaceutical Journal, 2023)
Conventional chemotherapy is ineffective for colorectal cancer as the drug moiety does not reach its intended site. 5-Fluorouracil (5-FU) microspheres aimed at colon-specific drug delivery have been developed by using the solvent evaporation technique in this study. The influence of utilizing different percentages of resistant starch-pectin polymer on the drug loading, encapsulation efficiency, and release behavior of the drug was investigated. The characterization of prepared microspheres was done by shape, surface morphology, drug loading, encapsulation efficiency and in vitro drug release studies. Drug-polymer interactions and drug stability were investigated by Differential Scanning Calorimetry (DSC) and FTIR spectroscopy. The 5-Fluorouracil polymeric microspheres that were formulated utilizing a resistant starch (RS) and pectin polymer displayed ideal physicochemical properties and spherical particles. The targeted microspheres demonstrated a high drug loading, encapsulation efficiency, and a satisfactory drug release pattern over the time period of 8 hours. Studies on drug release conducted under conditions that simulate stomach to colon transit have demonstrated that the drug was prevented from being released in the physiological conditions of the stomach and small intestine. Creating a new multiparticulate system using RS-pectin microspheres in order to forecast the protection that the combination might provide to the dosage form that will ensure localized drug release in the colon. Finally, it was found that the 5-Fluorouracil polymeric microsphere is a suitable microcarrier for effective colon-specific drug delivery tools with increased chemotherapeutic efficacy.Bangladesh Pharmaceutical Journal 26(1): 36-44, 2023 (January)